Structure refinement of fly ash in connection with its reactivity in geopolymerization. (December 2020) - Jin, Yu; Feng, Weipeng; Zheng, Dapeng; Dong, Zhijun; Cui, Hongzhi
Highlights: Thermal history of fly ash has significant impact on its glass structure. Peralkaline, peraluminous and silicate glass structures coexist in fly ash. The reactivity of fly ash is indexed by NBO/T modelled in a simplified glass setup. Abstract: It's an oversimplification to evaluate the reactivity of fly ash in geopolymerization using bulk elemental ratios like Si/Al. In this study, quantitative XRD by means of Rietveld refinement was employed to proportionate the mineral and glass phases of five fly ashes. The chemical environment of Si and Al in the fly ashes was investigated by 29 Si and 27 Al MAS NMR spectra. By counting the contributions of Al phase from mullite, the proportion of different coordination states of Al in the glass phase was speculated. The results reveal that the coordination number of Al is directly associated with the amount of alkali cations present in the glass phase for the most fly ashes, whereby higher the alkali content, the more four fold coordinated Al species are present in the system. Five and six fold coordinated Al as well as highly polymerized silicate species are also present in the glass structure of the fly ash. All these results point to an inherent inhomogeneous glass structure in fly ash. Despite that, a reactivity index derived from the NBO/T ratio (N on-B ridging O xygen per T etrahedral network former, e.g. SiO4 4-, AlO4 5- ) modelled in a simplified glass setup, correlates well with the reaction heat of the geopolymers.